Development and testing of an electrode for determination of potassium chloride and potassium bromide - Pérez-Saavedra, José de Jesús (2014)
To improve the potentiometric method for measuring potassium chloride and potassium bromide a combination electrode is designed, using as an indicator electrode Silver, and Copper/Copper nitrate as a reference electrode, where the electrolyte of the electrode do not interfere in the measurement and at the same time we can decrease to quantify volumes while eliminating salt bridge. In the results of the equivalence point volumes with conventional assembly and electrode developed, statistical Student´s t-test with 95 % significance level, is applied, resulting no significant difference with that level of reliance between methods.